Perovskite solar cell and preparation method thereof
By introducing tetramethylthiuram disulfide into the PCBM electron transport layer and induced reduction under ultraviolet light to form sulfur radicals, n-type doping of PCBM is achieved, which solves the problem of low carrier mobility and conductivity of the PCBM electron transport layer, and significantly improves the conversion efficiency of perovskite solar cells.
Patent Information
- Application Number
- CN202510093476.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
AI Technical Summary
The carrier mobility and conductivity in the PCBM electron transport layer are low, resulting in charge recombination loss and interface charge accumulation, reducing the conversion efficiency of perovskite solar cells.
The reduction of sulfur radicals under ultraviolet light is induced by tetramethylthiuram disulfide, n-type doping of PCBM is achieved, forming an n-type doping PCBM electron transport layer with high conductivity and high electron mobility.
It significantly inhibits charge recombination and interfacial charge accumulation, and improves the conversion efficiency of perovskite solar cells.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solar cells, and in particular relates to a perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have attracted much attention and developed rapidly internationally due to their outstanding advantages such as low cost, easy preparation and excellent photoelectric performance. Among them, the conversion efficiency of single-junction perovskite solar cells has increased from 3.8% in 2009 to more than 15% in 2020. At present, perovskite solar cells mainly include two types of structures: upright and inverted. Among them, the upright structure includes transparent conductive glass, electron transport layer, light absorption layer, hole transport layer and electrode in sequence, and the inverted structure includes transparent conductive glass, hole transport layer, light absorption layer, electron transport layer and electrode in sequence. Fullerene and its derivatives are widely used in organic solar cells because of their excellent electron extraction ability. [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) is a fullerene derivative with high electron mobility. It is often used as an electron acceptor for electron transport in inverted perovskite solar cells. It can form a good phase separation with common polymer donor materials. However, PCBM is easy to agglomerate in solution and exhibits a relatively low ionization barrier. After the PCBM solution is coated to form a PCBM electron transport layer, the carrier mobility and conductivity are low, which will increase charge recombination losses and interfacial charge accumulation, resulting in low conversion efficiency of solar cells. Summary of the invention
[0003] In view of the problems that the carrier mobility and conductivity in the PCBM electron transport layer involved in the above-mentioned prior art are low, resulting in the PCBM interface charge recombination loss and high interface charge accumulation, the present invention will provide a perovskite solar cell and a preparation method thereof.
[0004] To achieve the above purpose, the following technical solutions are specifically included:
[0005] The invention provides a perovskite solar cell, which comprises transparent conductive glass, a hole transport layer, a perovskite light absorption layer, an electron transport layer, an ITO film layer and an electrode layer in sequence, wherein the electron transport layer comprises an n-type doped PCBM electron transport layer, and the n-type doped PCBM electron transport layer is obtained by generating free radical-doped PCBM by tetramethylthiuram disulfide under ultraviolet induction.
[0006] The present invention achieves n-type doping of PCBM by inducing reduction of sulfur free radicals by tetramethylthiuram disulfide under ultraviolet light to obtain an n-type doped PCBM electron transport layer. The n-type doped PCBM electron transport layer exhibits high electrical conductivity and electron mobility, significantly inhibits charge recombination and interface charge accumulation, and lays a foundation for improving the conversion efficiency of perovskite solar cells.
[0007] Preferably, the transparent conductive glass comprises FTO glass.
[0008] Preferably, the hole transport layer comprises a NiO film layer.
[0009] Preferably, the hole transport layer has a thickness of 10-30 nm.
[0010] Preferably, the perovskite light absorbing layer comprises APbX3, A is a formamidine group (FA + ), cesium ion (Cs + ), X is Cl - Br - ,I - At least one of .
[0011] Preferably, the thickness of the perovskite light absorbing layer is 200-500 nm.
[0012] Preferably, the thickness of the electron transport layer is 10-30 nm.
[0013] Preferably, the thickness of the ITO film layer is 100-200 nm.
[0014] Preferably, the electrode layer comprises a copper electrode layer.
[0015] Preferably, the thickness of the electrode layer is 20-50 nm.
[0016] The present invention also provides a method for preparing a perovskite solar cell, comprising the following steps:
[0017] (1) depositing a hole transport layer on a transparent conductive glass by magnetron sputtering;
[0018] (2) coating the hole transport layer with a perovskite solution to obtain a perovskite light absorbing layer;
[0019] (3) uniformly mixing tetramethylthiuram disulfide and PCBM to obtain an electron transport layer precursor solution; irradiating the electron transport layer precursor solution with ultraviolet rays, and then coating the solution on the perovskite light absorbing layer and drying the solution to obtain an electron transport layer;
[0020] (4) depositing an ITO film layer on the electron transport layer by magnetron sputtering;
[0021] (5) Depositing an electrode layer on the ITO film layer by magnetron sputtering.
[0022] In the preparation method of the present invention, when preparing the electron transport layer, tetramethylthiuram disulfide (TMDS) is introduced into the PCBM solution, and then the TMDS is reduced to form thiol free radicals by ultraviolet irradiation, thereby realizing n-doping modification of PCBM. The obtained n-type doped PCBM electron transport shows enhanced conductivity and electron mobility, and significantly inhibits charge recombination.
[0023] Preferably, in step (1), the magnetron sputtering includes the following process parameters: sputtering power is 10-30KW, coating speed is 5-15mm / s, and voltage is 300-400V.
[0024] Preferably, in step (2), the perovskite solution comprises a compound with a perovskite structure and a solvent, the compound with a perovskite structure comprises at least one of CH5IN2, CH5BrN2, CsCl, CsBr, CsI, PbCl2, PbI2, and PbBr2, and the solvent comprises at least one of DMF and DMSO.
[0025] Further preferably, the perovskite solution comprises CH5IN2, CH5BrN2, CsBr, CsI, PbI2 and PbBr2, and the molar ratio of CH5IN2, CH5BrN2, CsBr, CsI, PbI2 and PbBr2 is CH5IN2:CH5BrN2:CsBr:CsI:PbI2:PbBr2=(0.4-0.5):(0.3-0.4):(0.1-0.2):(0.05-0.1):(0.5-0.8):(0.2-0.6), and the concentration of CH5IN2 in the perovskite solution is 1-2 mo / L.
[0026] Preferably, the solvent comprises DMF and DMSO, and the volume ratio of DMF to DMSO is 3-5:1.
[0027] Preferably, in step (2), the mixture is further filtered through 0.22 μm PTFE (polytetrafluoroethylene).
[0028] Preferably, in step (2), the coating method includes at least one of blade coating, spin coating, slit coating and spray coating.
[0029] Preferably, in step (3), the volume ratio of tetramethylthiuram disulfide to PCBM is (0.5-2):(98-99.5).
[0030] The CAS number of tetramethylthiuram disulfide is 137-26-8. Tetramethylthiuram disulfide induces the reduction of sulfur radicals under ultraviolet light to achieve n-type doping of PCBM. Under the above dosage of tetramethylthiuram disulfide, the surface of the electron transport layer shows high carrier mobility and conductivity.
[0031] Preferably, in step (3), the mixing method includes centrifugal mixing, and the rotation speed of the centrifugal mixing is 2000rpm-3000rpm.
[0032] Preferably, in step (3), the ultraviolet irradiation time is 30-180 minutes.
[0033] Preferably, in step (3), the coating method includes at least one of blade coating, spin coating, slit coating and spray coating.
[0034] Preferably, in step (3), the drying method is to dry in a nitrogen atmosphere at 70-80° C. for 10-120 seconds.
[0035] Preferably, in step (4), the magnetron sputtering includes the following process parameters: sputtering power is 5-30KW, coating speed is 5-15mm / s, and voltage is 300-400V.
[0036] Preferably, in step (5), the magnetron sputtering includes the following process parameters: sputtering power is 5-30KW, coating speed is 5-15mm / s, and voltage is 300-400V.
[0037] Compared with the prior art, the present invention has the following beneficial effects: the present invention achieves n-type doping of PCBM by inducing reduction of sulfur radicals by tetramethylthiuram disulfide under ultraviolet light to obtain an n-type doped PCBM electron transport layer, and the n-type doped PCBM electron transport layer exhibits high electrical conductivity and electron mobility, significantly inhibits charge recombination and interface charge accumulation, and lays a foundation for improving the conversion efficiency of perovskite solar cells. DETAILED DESCRIPTION
[0038] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0039] Example 1
[0040] A method for preparing a perovskite solar cell comprises the following steps:
[0041] (1) A NiO film with a thickness of 15 nm was deposited on FTO glass (fluorine-doped tin oxide coated glass) by magnetron sputtering as a hole transport layer for transporting holes, wherein the magnetron sputtering power was 15 KW, the magnetron sputtering coating speed was 10 mm / s, and the voltage was 350 V;
[0042] (2) preparing a mixed solvent of DMF (C3H7NO) and DMSO (C2H6OS) at a volume ratio of 4:1; adding FAI (CH5IN2, formamidine hydroiodide), FABr (CH5BrN2, formamidine hydrobromide), CsI, CsBr, PbI2 and PbBr2 to the mixed solvent at a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 to obtain a FAI concentration of 1.4 mol / L, and filtering with 0.22 μm PTFE (polytetrafluoroethylene); applying the filtered solution on a NiO film layer with a film thickness of 400 nm to obtain a perovskite light-absorbing layer, which reacts with sunlight to generate electrons and holes;
[0043] (3) Tetramethylthiuram disulfide (TMDS) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) were mixed in a volume ratio of 1:99, and then centrifuged at a speed of 2500 rpm. After the solution was mixed, it was irradiated with ultraviolet light for 125 minutes; then the ultraviolet irradiated solution was coated on the perovskite film layer through a slit, and the film layer was dried at 75°C in a clean N2 atmosphere for 50 seconds to obtain an electron transport layer with a film thickness of 20 nm;
[0044] (4) depositing a layer of ITO (tin-doped indium oxide) on the electron transport layer by magnetron sputtering, with a film thickness of 150 nm, wherein the magnetron sputtering power is 9 kW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V;
[0045] (5) A Cu film layer is deposited on the ITO film layer by magnetron sputtering as an electrode layer with a thickness of 30 nm. The magnetron sputtering power is 25 KW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V. Finally, a perovskite solar cell is obtained.
[0046] Example 2
[0047] The difference between this embodiment and embodiment 1 is that, in this embodiment, tetramethylthiuram disulfide (TMDS) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) are mixed at a volume ratio of 0.5:99.5, and the specific steps are as follows:
[0048] (1) A NiO film with a thickness of 15 nm was deposited on FTO glass (fluorine-doped tin oxide coated glass) by magnetron sputtering as a hole transport layer for transporting holes, wherein the magnetron sputtering power was 15 KW, the magnetron sputtering coating speed was 10 mm / s, and the voltage was 350 V;
[0049] (2) preparing a mixed solvent of DMF (C3H7NO) and DMSO (C2H6OS) at a volume ratio of 4:1; adding FAI (CH5IN2, formamidine hydroiodide), FABr (CH5BrN2, formamidine hydrobromide), CsI, CsBr, PbI2 and PbBr2 to the mixed solvent at a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 to obtain a FAI concentration of 1.4 mol / L, and filtering with 0.22 μm PTFE (polytetrafluoroethylene); applying the filtered solution on a NiO film layer with a film thickness of 400 nm to obtain a perovskite light-absorbing layer, which reacts with sunlight to generate electrons and holes;
[0050] (3) Tetramethylthiuram disulfide (TMDS) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) were mixed in a volume ratio of 0.5:99.5, and then centrifuged at a speed of 2500 rpm. After the solution was mixed, it was irradiated with ultraviolet light for 125 minutes; then the ultraviolet irradiated solution was coated on the perovskite film layer through a slit, and the film layer was dried at 75°C in a clean N2 atmosphere for 50 seconds to obtain an electron transport layer with a film thickness of 20 nm;
[0051] (4) depositing a layer of ITO (tin-doped indium oxide) on the electron transport layer by magnetron sputtering, with a film thickness of 150 nm, wherein the magnetron sputtering power is 9 kW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V;
[0052] (5) A Cu film layer is deposited on the ITO film layer by magnetron sputtering as an electrode layer with a thickness of 30 nm. The magnetron sputtering power is 25 KW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V. Finally, a perovskite solar cell is obtained.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that, in this embodiment, tetramethylthiuram disulfide (TMDS) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) are mixed at a volume ratio of 0.5:99.5, and the specific steps are as follows:
[0055] (1) A NiO film with a thickness of 15 nm was deposited on FTO glass (fluorine-doped tin oxide coated glass) by magnetron sputtering as a hole transport layer for transporting holes, wherein the magnetron sputtering power was 15 KW, the magnetron sputtering coating speed was 10 mm / s, and the voltage was 350 V;
[0056] (2) preparing a mixed solvent of DMF (C3H7NO) and DMSO (C2H6OS) at a volume ratio of 4:1; adding FAI (CH5IN2, formamidine hydroiodide), FABr (CH5BrN2, formamidine hydrobromide), CsI, CsBr, PbI2 and PbBr2 to the mixed solvent at a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 to obtain a FAI concentration of 1.4 mol / L, and filtering with 0.22 μm PTFE (polytetrafluoroethylene); applying the filtered solution on a NiO film layer with a film thickness of 400 nm to obtain a perovskite light-absorbing layer, which reacts with sunlight to generate electrons and holes;
[0057] (3) Tetramethylthiuram disulfide (TMDS) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) were mixed in a volume ratio of 2:98, and then centrifuged at a speed of 2500 rpm. After the solution was mixed, it was irradiated with ultraviolet light for 125 minutes; then the ultraviolet irradiated solution was coated on the perovskite film layer through a slit, and the film layer was dried at 75°C in a clean N2 atmosphere for 50 seconds to obtain an electron transport layer with a film thickness of 20 nm;
[0058] (4) depositing a layer of ITO (tin-doped indium oxide) on the electron transport layer by magnetron sputtering, with a film thickness of 150 nm, wherein the magnetron sputtering power is 9 kW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V;
[0059] (5) A Cu film layer is deposited on the ITO film layer by magnetron sputtering as an electrode layer with a thickness of 30 nm. The magnetron sputtering power is 25 KW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V. Finally, a perovskite solar cell is obtained.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that in this comparative example, tetramethylthiuram disulfide (TMDS) is not added to dope [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), and the specific steps are as follows:
[0062] (1) A NiO film with a thickness of 15 nm was deposited on FTO glass (fluorine-doped tin oxide coated glass) by magnetron sputtering as a hole transport layer for transporting holes, wherein the magnetron sputtering power was 15 KW, the magnetron sputtering coating speed was 10 mm / s, and the voltage was 350 V;
[0063] (2) preparing a mixed solvent of DMF (C3H7NO) and DMSO (C2H6OS) at a volume ratio of 4:1; adding FAI (CH5IN2, formamidine hydroiodide), FABr (CH5BrN2, formamidine hydrobromide), CsI, CsBr, PbI2 and PbBr2 to the mixed solvent at a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 to obtain a FAI concentration of 1.4 mol / L, and filtering with 0.22 μm PTFE (polytetrafluoroethylene); applying the filtered solution on a NiO film layer with a film thickness of 400 nm to obtain a perovskite light-absorbing layer, which reacts with sunlight to generate electrons and holes;
[0064] (3) coating a [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) solution on the perovskite film layer through a slit, and drying the film layer at 75°C in a clean N2 atmosphere for 50 seconds to obtain an electron transport layer with a film thickness of 20 nm;
[0065] (4) depositing a layer of ITO (tin-doped indium oxide) on the electron transport layer by magnetron sputtering, with a film thickness of 150 nm, wherein the magnetron sputtering power is 9 kW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V;
[0066] (5) A Cu film layer is deposited on the ITO film layer by magnetron sputtering as an electrode layer with a thickness of 30 nm. The magnetron sputtering power is 25 KW, the magnetron sputtering coating speed is 10 mm / s, and the voltage is 350 V. Finally, a perovskite solar cell is obtained.
[0067] Performance test: The electron mobility of the electron transport layer was measured by a Hall meter, and the conductivity of the electron transport layer was measured by a four-probe test. The test results are shown in Table 1.
[0068] Table 1
[0069] Group <![CDATA[Conductivity / (S / m 3 )]]> <![CDATA[Electron mobility / (cm 2 / (V·s))]]> Example 1 <![CDATA[4.0×10 -3 ]]> 48 Example 2 <![CDATA[3.8×10 -3 ]]> 45 Example 3 <![CDATA[5.1×10 -3 ]]> 59 Comparative Example 1 <![CDATA[2.7×10 -3 ]]> 32
[0070] It can be seen from Examples 1-3 and Comparative Example 1 that the present invention introduces tetramethylthiuram disulfide (TMDS) into the PCBM solution, and then induces the reduction of TMDS to form sulfur free radicals through ultraviolet irradiation, thereby achieving n-doping modification of PCBM. The resulting n-type doped PCBM electron transport exhibits enhanced conductivity and electron mobility, significantly inhibits charge recombination, and is beneficial to improving the conversion efficiency of perovskite batteries.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A perovskite solar cell, characterized in that: The invention comprises transparent conductive glass, a hole transport layer, a perovskite light absorption layer, an electron transport layer, an ITO film layer and an electrode layer in sequence. The electron transport layer comprises an n-type doped PCBM electron transport layer. The n-type doped PCBM electron transport layer is obtained by generating free radical doped PCBM by tetramethylthiuram disulfide under ultraviolet induction.
2. The perovskite solar cell according to claim 1, characterized in that The hole transport layer comprises a NiO film layer, and the thickness of the hole transport layer is 10-30 nm.
3. The perovskite solar cell according to claim 1, characterized in that The perovskite light-absorbing layer comprises APbX3, A is at least one of a formamidite group and a cesium ion, and X is Cl - Br - ,I - At least one of the following; the thickness of the perovskite light absorbing layer is 200-500nm.
4. The perovskite solar cell according to claim 1, characterized in that The thickness of the electron transport layer is 10-30 nm.
5. The perovskite solar cell according to claim 1, characterized in that The transparent conductive glass includes FTO glass; the thickness of the ITO film layer is 100-200nm; the electrode layer includes a copper electrode layer, and the thickness of the electrode layer is 20-50nm.
6. A method for preparing a perovskite solar cell according to any one of claims 1 to 5, characterized in that: The steps include: (1) depositing a hole transport layer on a transparent conductive glass by magnetron sputtering; (2) coating a perovskite solution on the hole transport layer to obtain a perovskite light absorbing layer; (3) uniformly mixing tetramethylthiuram disulfide and PCBM to obtain an electron transport layer precursor solution; irradiating the electron transport layer precursor solution with ultraviolet rays, and then coating the solution on the perovskite light absorbing layer and drying the solution to obtain an electron transport layer; (4) depositing an ITO film layer on the electron transport layer by magnetron sputtering; (5) Depositing an electrode layer on the ITO film layer by magnetron sputtering.
7. The method for preparing a perovskite solar cell according to claim 6, characterized in that: Include at least one of the following: In step (1), the magnetron sputtering includes the following process parameters: sputtering power is 10-30KW, coating speed is 5-15mm / s, and voltage is 300-400V; In step (2), the perovskite solution comprises a compound having a perovskite structure and a solvent, wherein the compound having a perovskite structure comprises at least one of CH5IN2, CH5BrN2, CsCl, CsBr, CsI, PbCl2, PbI2, and PbBr2, and the solvent comprises at least one of DMF and DMSO; The perovskite solution includes CH5IN2, CH5BrN2, CsBr, CsI, PbI2 and PbBr2, and the molar ratio of CH5IN2, CH5BrN2, CsBr, CsI, PbI2 and PbBr2 is CH5IN2:CH5BrN2:CsBr:CsI:PbI2:PbBr2=(0.4-0.5):(0.3-0.4):(0.1-0.2):(0.05-0.1):(0.5-0.8):(0.2-0.6), and the concentration of CH5IN2 in the perovskite solution is 1-2 mo / L.
8. The method for preparing a perovskite solar cell according to claim 6, characterized in that: Include at least one of the following: In step (2), the coating method includes at least one of scraping, spin coating, slit coating, and spray coating.
9. The method for preparing a perovskite solar cell according to claim 6, characterized in that: Include at least one of the following: In step (3), the volume ratio of tetramethylthiuram disulfide to PCBM is (0.5-2):(98-99.5); In step (3), the mixing method includes centrifugal mixing; In step (3), the ultraviolet irradiation time is 30-180min; In step (3), the coating method includes at least one of blade coating, spin coating, slit coating, and spray coating; In step (3), the drying method is to dry in a nitrogen atmosphere at 70-80°C for 10-120s.
10. The method for preparing a perovskite solar cell according to claim 6, characterized in that: Include at least one of the following: In step (4), the magnetron sputtering includes the following process parameters: sputtering power is 5-30KW, coating speed is 5-15mm / s, and voltage is 300-400V; In step (5), the magnetron sputtering includes the following process parameters: sputtering power is 5-30KW, coating speed is 5-15mm / s, and voltage is 300-400V.